TBC-Free Neighborhood: Community Empowerment in TBC Screening and Early Detection Efforts in Kota Wetan Sub-District, Garut City - Witdiawati, Witdiawati; Purnama, Dadang; Noor, Rohmahalia M (GUYUB: Journal of Community Engagement, 2024)
One of the top 10 causes of death worldwide is Tuberculosis (TB). One of the strategic programs to eliminate TB is by increasing community involvement in TB control. This community service activity was conducted in RW 15, Kota Wetan Village, Garut Regency, using a community empowerment method with a series of TB health education and door-to-door TB screening activities. The results of the health education activities among 25 participants showed an increase in pre-test and post-test scores, with an average of 76.25 rising to 91.25. Residents aged over 15 years who participated in the screening consisted of 44 men (49%) and 46 women (51%). A total of 39 sputum samples were collected and then distributed to the community health center for laboratory analysis. The results of the TB screening based on the sputum sample test found 4 positive TB SO cases.